1997
DOI: 10.1152/ajpheart.1997.272.2.h728
|View full text |Cite
|
Sign up to set email alerts
|

Non-insulin-dependent diabetes and hyperglycemia impair rat intestinal flow-mediated regulation

Abstract: Release of nitric oxide from small arteries and larger arterioles of the intestine maintains their dilation and thereby supports mucosal blood flow. This flow-dependent mechanism can be studied by isosmotic replacement of sodium chloride with mannitol over the mucosa to lower mucosal metabolism and blood flow requirements. We tested the hypothesis that flow-mediated regulation is impaired in the non-insulin-dependent Zucker fatty diabetic (ZFD) male rats because of their marginally impaired endothelium-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…22 Our observations are in agreement with previous studies demonstrating an endothelial dysfunction in obese Zucker rat, especially in the NO pathway. 20,23 An excessive ROS production might also cause this low NO bioavailability. This was evidenced by a rise in DHE staining and NADPH oxidase (gp91 and p67) expression in mesenteric arteries, as well as by the restoration of ACh-induced dilation by antioxidant treatments, as shown in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…22 Our observations are in agreement with previous studies demonstrating an endothelial dysfunction in obese Zucker rat, especially in the NO pathway. 20,23 An excessive ROS production might also cause this low NO bioavailability. This was evidenced by a rise in DHE staining and NADPH oxidase (gp91 and p67) expression in mesenteric arteries, as well as by the restoration of ACh-induced dilation by antioxidant treatments, as shown in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study by Andrews et al (Andrews et al, 2000) reports that vasodilation of the perfused hindquarter in response to acetylcholine was increased in diabetic obese Zucker rats when compared to lean Zucker rats. Others (Jin and Bohlen, 1997;Frisbee, 2001;Frisbee and Stepp, 2001), however, have shown selective impairment in nitric oxide synthasedependent dilation of peripheral blood vessels during type II diabetes mellitus. Jin and Bohlen (Jin and Bohlen, 1997) examined reactivity of intestinal arterioles in response to changes in blood flow and acetylcholine in lean and diabetic obese Zucker rats.…”
Section: Effects Of Type II Diabetes Mellitus On Responses Of Periphementioning
confidence: 99%
“…Others (Jin and Bohlen, 1997;Frisbee, 2001;Frisbee and Stepp, 2001), however, have shown selective impairment in nitric oxide synthasedependent dilation of peripheral blood vessels during type II diabetes mellitus. Jin and Bohlen (Jin and Bohlen, 1997) examined reactivity of intestinal arterioles in response to changes in blood flow and acetylcholine in lean and diabetic obese Zucker rats. These investigators found that flow-mediated and acetylcholine-induced dilation of intestinal arterioles were impaired in obese Zucker rats when compared to lean Zucker rats (Jin and Bohlen, 1997).…”
Section: Effects Of Type II Diabetes Mellitus On Responses Of Periphementioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] However, human obesity primarily results from alterations in a combination of different genes (i.e., polygenic) that interact with environmental factors such as diet to promote aspects of the metabolic syndrome. Outbred Sprague-Dawley rats respond to a moderately high fat (MHF) diet with either an obesityprone (OP) or obesity-resistant (OR) phenotype.…”
Section: Introductionmentioning
confidence: 99%